2007
DOI: 10.1016/j.physleta.2007.04.055
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dissipation on quantum transmission resonance

Abstract: Quantum transmissions of a free particle passing through a rectangular potential barrier with dissipation are studied using a path decomposition technique. Dissipative processes strongly suppress the transmission probability at resonance just above the barrier resulting in an unexpected reduction of the mean traversal time through the potential barrier.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Thus, the probability for finding the particles in the given space interval [−1, 1] for a given time is suppressed by dissipation resulting into the reduction of the dwell time. By using a different method, such a behavior has already been reported in [32] where the mean transversal time through a rectangular barrier reduces with dissipation. When stochastic fluctuations are taken into account, the width of the probability distribution will have an additional contribution, Eq.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Thus, the probability for finding the particles in the given space interval [−1, 1] for a given time is suppressed by dissipation resulting into the reduction of the dwell time. By using a different method, such a behavior has already been reported in [32] where the mean transversal time through a rectangular barrier reduces with dissipation. When stochastic fluctuations are taken into account, the width of the probability distribution will have an additional contribution, Eq.…”
Section: Resultsmentioning
confidence: 73%
“…Dissipative tunnelling through a parabolic repeller has been studied via quantum Langevin equation [30], realized by resistively shunted Josephson junctions, and using the Caldirola-Kanai [31] and Kostin [10] approaches. On the other hand, very recently, investigation of dissipative tunnelling times through different approaches have attracted many researchers [32][33][34][35][36]. Transmission probabilities through tunnelling and above barrier as well as dwell times are then calculated at different bath temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Using a somewhat similar approach for dissipation with the latter given by a frictional force as in [11], in the present work we shall show that the counter-intuitive result found in [20] can indeed be explained.…”
mentioning
confidence: 56%
“…In [18], studying the dissipative tunneling through an inverted harmonic oscillator in context with ion transport at nanoscale, the authors showed that the phase time delay can be estimated directly in terms of a frictional coefficient. The average dwell time, τ D , through a rectangular potential barrier using a path decomposition technique was investigated in [20] leading to the counter-intuitive result that τ D in the presence of dissipation becomes smaller than that in a non-dissipative case. The traversal time behaviour for a rectangular barrier with energy losses included was described in [21] within a semiclassical approach with dissipation included in the form of a frictional force.…”
mentioning
confidence: 99%
“…In particular, dissipative tunnelling through a parabolic repeller has been studied via quantum Langevin equation [54], in resistively shunted Josephson junctions, and using the CK [55] and Kostin [47] approaches. Investigation of dissipative tunnelling times through different approaches have attracted many researchers [56][57][58][59][60]. Thus, Baskoutas and Jannussis [61] and Papadopoulos [55], Tokieda and Hagino [62] have considered similar theoretical frameworks.…”
Section: Introductionmentioning
confidence: 99%